P01.058 Higher immune associated markers (PD-L1, PD-1, TMB, MSI) in gliosarcoma compared to glioblastoma. (19th September 2018) - Phuphanich, S; Sanai, N; Xiu, J; Mittal, S; Michelhaugh, S; Subramaniam, D S; Pandey, M K; Kesari, S; Heimberger, A B; Gatalica, Z; Korn, W M; Sumrall, A L
Abstract: Background: Gliosarcomas (GS) are rare histological glioblastoma (GB) variants with glial and mesenchymal components. GS has been reported to have a similar genetic profile to primary GB. In a small series of GS, tissue from both the glial and sarcomatous components revealed PTEN and TP53 mutations, and p16 deletion in both tissue components. Studies on systematic comparison of GS and GB are scarce. Material and Methods: A total of 44 GS and 1449 GB tumors profiled by Caris Life Sciences from 2013 to 2017 were tested by NextGen sequencing (NGS, 592 or 45 gene panels) for mutations and gene amplification. Tumor mutational burden (TMB) was calculated using somatic nonsynonymous missense mutations. Microsatellite instability (MSI) was tested by NGS. PD-L1 immunohistochemistry (SP142) was done on tumor cells and PD-1 on tumor-infiltrating lymphocytes. MGMT promoter methylation was tested by pyrosequencing; EGFRvIII and gene fusions by RNA-sequencing (ArcherDx FusionPlex). Results: Mutations in 16 genes were seen in GS: the most frequent were TP53 (41 %), NF1 (33 %), PTEN (29 %), RB1 (10%), PTPN11 (7%) and PIK3CA (5%). Amplification of CDK4 (8%), MET (8%) and MDM2 (4%) were seen and NTRK1 fusion was seen in 1 of 20 (5%) GS tumors tested with RNA-SEQ. When compared to GB, GS had significantly higher NF1 (GS: 33% vs. GB 14%, p = 0.008) and PTPN11 (7% vs. 2%, p = 0.04) mutations. Furthermore, immune-associated markers: PD-L1 (38.5% vs. 16.3%, p = 0.0003), PD-1 (75% vs. 49.2%, p = 0.01) and MSI-High (3.8 vs. 0.5%, p = 0.038) were significantly higher in GS; TMB-High (> = 17mut/MB) (7.7 vs. 2.9%, p = 0.17) showed a trend. In contrast, EGFR alterations including EGFR amplification (7.7 & 37.2%, p = 0.0021) and EGFR mutations (0 vs. 11%, p = 0.02) were less prevalent in GS than GB as also EGFRvIII (5.9 vs. 18.9%, p = 0.055), EGFR fusions (0 vs. 9%, p > 0.05), IDH1 mutation (0 vs. 7.8%, p = 0.054) and MGMT promoter methylation (34.1 & 45%, p > 0.05). Conclusion: In summary, based on our analysis, GS appears to be a distinct biological entity with unique genomic features and immunophenotype compared to GB. These results also provide insight into potential immune therapy, based on the association of PD-1/PD-L1 with other key genetic alterations in this population, which warrants further investigation in clinical studies.